(untitled) (BIMRAD Journal, 2025)
The destruction of marine ecosystems by Illegal, Unreported and Unregulated (IUU) fishing is a real concern in the Bay of Bengal (BoB). Bangladesh, ranked 47th on the IUU Fishing Index, is one of the most affected nations, with both local and foreign vessels contributing to this issue. The study aims at identifying key drivers behind IUU fishing in the region and examine how well National Plan of Action to combat IUU fishing (NPOA-IUU) under Bangladesh works. The research used a mixed-methods approach, combining quantitative analysis of IUU fishing intensity scores from the IUU Fishing Index and qualitative interviews with stakeholders such as government officials, fisheries experts, and local fishers. To analyse the quantitative data simple descriptive statistical methods, including frequency and percentage distribution, as well as basic measures such as mean were used to summarize the findings. On the other hand, the qualitative data was processed using a systematic logical approach to explain the issue properly. The result of the present study indicates that foreign fishing vessel scores 04 for most IUU fishing intensity out of 05. IUU fishing from unreported and unregulated methods achieved a score of 03 while its destructive fishing practices scored at level 02. IUU fishing was negatively influenced by low profit, uncertain climate and fish availability at the same time indiscriminate fishing with destructive fishing methods. Elsewhere, the study also assessed applicability and operability of NPOA-IUU using SMART approach and reveals that the NPOA-IUU is moderately effective, with an implementation that places loads on resources, effort and present capacity. In order to fight IUU fishing, Bangladesh must improve law enforcement and monitoring capabilities and advocate for sustainable fisheries. BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-178-196